Secret and Overt Information Acquisition in Financial Markets - Xiong, Yan; Yang, Liyan (Review of Financial Studies, 2023)
Abstract We study the observability of investors’ information-acquisition activities in financial markets. Improving observability leads to two strategic effects on information acquisition: (1) the pricing effect, which arises from interactions between investors and the market maker and can encourage or discourage information acquisition, and (2) the competition effect, which concerns interactions among investors and always encourages information acquisition. We apply our theory to study voluntary and mandatory disclosures of corporate site visits. When the competition effect dominates, investors voluntarily disclose their visits. When the pricing effect dominates, mandatory disclosure is effective. Our analysis sheds novel light on Regulation Fair Disclosure. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.